An experiment for observing quantum gravity phenomena using twin table-top 3D interferometers. (18th March 2021) - Vermeulen, S M; Aiello, L; Ejlli, A; Griffiths, W L; James, A L; Dooley, K L; Grote, H
Abstract: Theories of quantum gravity based on the holographic principle predict the existence of quantum fluctuations of distance measurements that accumulate and exhibit correlations over macroscopic distances. This paper models an expected signal due to this phenomenology, and details the design and estimated sensitivity of co-located twin table-top 3D interferometers being built to measure or constrain it. The experiment is estimated to be sensitive to displacements ∼ 1 0 − 19 m / H z in a frequency band between 1 and 250 MHz, surpassing previous experiments and enabling the possible observation of quantum gravity phenomena. The experiment will also be sensitive to MHz gravitational waves and various dark matter candidates.